Aplikasi Pemantauan Tong Sampah berasaskan IoT menggunakan Sensor Ultrasonik: IoT-based Garbage Bin Monitoring Application - Jailani, Fatin Hamizah; Kamaludin, Hazalila (Applied Information Technology And Computer Science, 2021)
The IoT-based Garbage Bin Monitoring Application is an application developed to make process of collecting waste from garbage bin in Pasar Awam Batu Pahat easier. It is important to collect waste regularly to avoid the increasing in amount of waste. Environment and human will be affected by large amount of waste not being collected. That is why this application is developed. Load cell sensor module HX711 is used to measure the weight of waste and ultrasonic sensor HC-SR04 is for measuring distance of waste from surface of garbage bin. Waste can be collected when the garbage bin is full to avoid waste overflow. Based on waterfall methodology, this application is developed by using Android Studio, using Java programming language and Google Firebase as the database. At the end of development, an IoT-based Garbage Bin Monitoring Application is successfully developed according to user requirement.